Comparative Effect of the Supervision of the Principal and Quality of Organizational Management in School Education - BUDI WIYONO, BAMBANG; BURHANUDDIN, BURHANUDDIN; MAISYAROH, MAISYAROH (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Improving the quality of education becomes a priority in the development of the education system in Indonesia. There are many factors that affect the quality of education. Consecutively, there are four variables of the quality of the management substance that influence the school achievement, namely the completeness of facility, the quality of learning process, the administration service, and the teachers quality. As a result, there is a positive influence of supervision and quality of organizational management substance on school performance. Partially, the quality of management substance has stronger influences than the supervision experience of the principals.RESUMEN Mejorar la calidad de la educación se convierte en una prioridad en el desarrollo del sistema educativo en Indonesia. Son muchos los factores que afectan la calidad de la educación. En consecuencia, hay cuatro variables de la calidad de la esencia de gestión que influyen en el rendimiento escolar, a saber, la integridad de la instalación, la calidad del proceso de aprendizaje, el servicio de administración y la calidad de los profesores. Como resultado, existe una influencia positiva de la supervisión y la calidad de la esencia de la gestión organizacional en el desempeño escolar. En parte, la calidad de la esencia de gestión tiene influencias más sólidas que la experiencia de supervisión de los directores.